Public Expenditure Following Disasters - Bevan, David; Cook, Samantha (World Bank, Washington, DC, 2015)
This paper focuses on the impact of disasters on public expenditures, and how this impact might be valued. The impact may involve changes in the composition of spending, concurrently and over time. It may also involve changes in the level of spending and the profile of this over time. In the latter case, the associated financing must also be taken into account. The changes of interest are those that would take place under a given sovereign disaster risk financing and insurance strategy, as opposed to what would take place otherwise. The paper concludes with some suggestions toward an operational framework for addressing these questions.